tDCS-induced enhancement of cognitive flexibility in autism: role of frontal lobe and associated neural circuits - Han, Yanan; Dong, Anqin; Xia, Chenyi; Zhang, Zhe; Hu, Wenjing; He, Tingli; Cui, Xinxin; Xu, Chengming; Xu, Hongyan; Zhou, Zhangying; Cheng, Danmeng; Zhang, Shuo; et al. (Frontiers in Behavioral Neuroscience, 2025)
BackgroundAutism spectrum disorder (ASD) is a neurodevelopmental disorder characterized by impaired social interaction and restricted, repetitive behaviors (RRBs). These symptoms may stem from cognitive flexibility deficits, with dysfunction in the prefrontal cortex (PFC) and related neural circuits proposed as underlying mechanisms.ObjectivesThis study examined whether transcranial direct current stimulation (tDCS) could enhance PFC activity and functional connectivity, thereby improving cognitive flexibility in a valproic acid (VPA)-induced ASD rat model.MethodsPregnant Sprague-Dawley rats were administered VPA (600 mg/kg, E12.5) or saline. VPA-exposed offspring exhibiting curved tails received tDCS and underwent behavioral tests, including the three-chamber social interaction test and cross-maze rule-shifting task, while local field potentials (LFPs) were recorded. Immunohistochemistry was performed to evaluate microglial activation (Iba1 +) and synaptic density (PSD95).ResultsValproic acid -exposed offspring displayed significant social interaction deficits and impaired cognitive flexibility, alongside disrupted functional connectivity in frontal-striato-hippocampal circuits. Neuroinflammatory analysis revealed elevated Iba1+ microglial density (p < 0.05) and increased PSD95 expression (p < 0.05). After tDCS intervention, VPA rats exhibited restored sociability and cognitive performance, normalized functional connectivity, and significantly reduced microglial activation (p < 0.05), though PSD95 levels were unaffected.ConclusionOur results indicate that tDCS ameliorates ASD-like phenotypes in VPA rats, potentially through microglial suppression and PFC network synchronization. These findings support neuromodulation as a promising therapeutic approach for ASD-related cognitive dysfunction.